2014
DOI: 10.1371/journal.pone.0113602
|View full text |Cite
|
Sign up to set email alerts
|

Is Nephrolithiasis an Unrecognized Extra-Articular Manifestation in Ankylosing Spondylitis? A Prospective Population-Based Swedish National Cohort Study with Matched General Population Comparator Subjects

Abstract: BackgroundAnkylosing spondylitis (AS) is associated with several extra-articular manifestations. Nephrolithiasis (NL) has not been recognized as one of those, however, several factors known to increase the risk of NL are at play in AS patients. The objective was to estimate rates and predictors of NL in Swedish patients with AS compared to the general population.Methods and FindingsWe performed a prospective population-based nationwide cohort study based on linkage of data from Swedish registries. 8,572 AS pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 30 publications
1
18
1
Order By: Relevance
“…An extra-articular involvement is common in inflammatory diseases. Although renal involvement has been shown in many studies on AS, the number of studies investigating the coexistence of renal calculi in AS is very limited [7][8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An extra-articular involvement is common in inflammatory diseases. Although renal involvement has been shown in many studies on AS, the number of studies investigating the coexistence of renal calculi in AS is very limited [7][8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showing an increased incidence of renal calculi in patients with AS have been published [7][8][9][10][11][12][13]. Jacobsen et al found the risk of nephrolithiasis in patients with AS to be more than twofold compared to the general population.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the result of another population-based study (sample of 8,572 AS patients) in Sweden indicated that 4.0% of the AS patients and 1.8% of the general population comparators had received a diagnosis of nephrolithiasis at the end of the study period. 16 Additionally, Liu et al 17 claimed that AS patients with DM or Crohn's disease were observed to have a higher risk of nephrolithiasis.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, several studies have shown that urolithiasis is indeed frequently observed among patients with AS [5][6][7]. Since urolithiasis may have a relapsing nature and may necessitate surgical intervention [8], it may cause significant morbidity beyond the morbidity caused by AS alone.…”
Section: Introductionmentioning
confidence: 99%